“I Have More Friends That Died Than Fingers and Toes”: Service Utilization Needs and Preferences for Violence and Substance Use Prevention Among Young Black Boys and Men - Emezue, Chuka N. (Journal of interpersonal violence, 2025)
Young Black men (YBM) disproportionately face the most severe forms and consequences of youth violence (YV) and substance use disorders, but are less likely to access and be retained in services for these high-risk behaviors. Investigating service uptake disparities and the role of barrier-reducing intervention delivery models is essential; so is understanding the service needs and preferences of YBM. This study explores the experiences of violence-involved and substance-disordered YBM and service providers working with them from racially and economically diverse communities, focusing on their service needs and preferences. Additionally, we examine the potential benefits and drawbacks of digital health interventions in addressing crucial structural barriers to service access and promoting equity for Black boys in high-violence environments. Individual interviews were conducted with 16 YBM (selected from a larger pool of 300 participants from a pilot study) and 7 service providers (four females, three males). Data analysis utilized an Interpretive Description (ID) approach guided by the Phenomenological Variant of Ecological Systems Theory (PVEST). Four themes emerged: (1) Revolving Doors and Histories of Violence; (2) Benefits of Violence: “You Do Something to Me, I Do Something to You”; (3) Positive and Negative Perceptions of Violence and Substance Use Prevention Programs; and (4) Need for Equity-Focused and Barrier-Mitigating Digital Health Interventions. Our findings identified avoidance mechanisms utilized by YBM at both individual and community levels and highlighted perceptions of existing community-based programs and digital interventions as crucial tools for mitigating barriers to care. This study also confirms the prevalence of critical service gaps and program uptake issues, even in cities with abundant programs. Thus emphasizing the need for equity-focused interventions co-designed with and for YBM in high-violence and substance use contexts.